Oxytocin administration during cesarean delivery: Randomized controlled trial to compare intravenous bolus with intravenous infusion regimen - Susmita Bhattacharya; Sarmila Ghosh; Debanjali Ray; Suchismita Mallik; Arpita Laha (Wolters Kluwer Medknow Publications, 2013)
Background: Oxytocin is routinely administered during cesarean delivery for uterine contraction. Adverse effects are known to occur after intravenous oxytocin administration, notably tachycardia, hypotension, and electrokardiogram (EKG) changes, which can be deleterious in high-risk patients. Aims and Objectives: To compare the hemodynamic changes and uterotonic effect of equivalent dose of oxytocin administered as an intravenous bolus versus intravenous infusion. Study Design: Randomized, double-blind, active controlled trial. Materials and Methods: Eighty parturients undergoing elective cesarean delivery, under spinal anesthesia, were randomly allocated to receive 3 IU of oxytocin either as a bolus intravenous injection over 15 seconds (group B, n = 40) or as an intravenous infusion over 5 minutes (group I, n = 40). Uterine tone was assessed as adequate or inadequate by an obstetrician. Intraoperative heart rate, non-invasive blood pressure, and EKG changes were recorded. These data were compared between the groups. Any other adverse events like chest pain, nausea, vomiting, and flushing were noted. Results: There was significant rise in heart rate and significant decrease in mean arterial pressure in bolus group compared to infusion group. Three patients in bolus group had EKG changes in the form of ST-T depression and 5 patients complained of chest pain. No such complications were found in infusion group. Conclusion: Bolus oxytocin (at a dose of 3 IU over 15 seconds) and infusion of oxytocin (at a dose of 3 IU over 5 minutes) have comparable uterotonic effect. However, the bolus regime shows significantly more adverse cardiovascular events.